2010
DOI: 10.1007/s00484-010-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of climate on durum wheat quality in Tuscany, Central Italy

Abstract: Climate and meteorological conditions greatly affect agricultural activities, modifying plant responses and determining the quantity and the quality of production. In this respect, the aim of this research was to analyze the quality of winter durum wheat (Triticum turgidum L. var. durum), in terms of protein content through the use of meteorological information. Meteorological conditions were described utilizing both local weather station data (air temperature, cumulated precipitation) and large-scale informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Moreover, the occurrence of a marked terminal water stress in grain filling under rainfed conditions in the first year may have determined also an improvement in the technological parameters. Finally, for the yellow index, the same trend reported for protein content was observed for pigment content, in agreement with Dexter and Matsuo (1977) and Dalla Marta et al (2011), who reported an association between protein content increase and an increase in pigment content.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the occurrence of a marked terminal water stress in grain filling under rainfed conditions in the first year may have determined also an improvement in the technological parameters. Finally, for the yellow index, the same trend reported for protein content was observed for pigment content, in agreement with Dexter and Matsuo (1977) and Dalla Marta et al (2011), who reported an association between protein content increase and an increase in pigment content.…”
Section: Discussionsupporting
confidence: 89%
“…M editerranean countries, where durum wheat is largely cultivated, are characterized by dry and hot summers alternating with humid and temperate winters (Ercoli et al, 2008). Due to this particular climatic trend, characterized by scarce water availability during the durum wheat grain‐filling period, predicting crop performance is challenging (Dalla Marta et al, 2011). As in other crops, an inverse relationship between grain yield and grain N concentration has been reported in durum wheat (Ehdaie and Waines, 2001; Triboï and Triboï‐Blondel, 2002, 2009; Martre et al, 2003; Triboï et al, 2006), and the degree of this relationship varies depending on soil fertility, water availability, and other environmental factors (Ehdaie and Waines, 2001).…”
mentioning
confidence: 99%
“…Dalla Marta et al . () found a correlation between durum wheat over Gibraltar and geopotential at 500 hPa. Through the use of teleconnection patterns, a number of studies have demonstrated that large‐scale variables have effects on crop production.…”
Section: Introductionmentioning
confidence: 84%
“…In Italy, durum wheat represents approximately 55 % of the total wheat production (http://www.ec.europa.eu/eurostat/ data), while in the European Union, as a whole, it only reaches 5 %. For these reasons in Italy, the weather effects on winter durum wheat are of primary interest (Dalla Marta et al, 2011). Winter durum wheat is cultivated in southern/central Italy and in some areas of northern Italy, with about 1.2 million hectares dedicated to this crop.…”
Section: Introductionmentioning
confidence: 99%